DIGITAL TECHNOLOGIES AND EMPLOYMENT: THE CASE OF UZBEKISTAN (International journal of artificial intelligence, 2025)
This article analyzes the impact of digital technologies on the labor market in Uzbekistan. The objective is to identify how digital technologies are transforming jobs, shaping the demand for new professions and skills, and assessing the readiness of the existing workforce. The methodology includes statistical data, government policies, and industry experts’ opinions. The study results show that digital technologies create new opportunities in the labor market, but obstacles such as skill gaps, infrastructure issues, and digital illiteracy remain.